2022
DOI: 10.1080/10408398.2022.2077300
|View full text |Cite
|
Sign up to set email alerts
|

Fermented food: Should patients with cardiometabolic diseases go back to an early neolithic diet?

Abstract: The material cannot be used for any other purpose without further permission of the publisher and is for private use only.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.https://eprints.gla.ac.uk/272027/ Deposited on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 209 publications
0
1
0
Order By: Relevance
“…Fermented foods based on lactic acid bacteria, such as sauerkraut, pickled cabbages, fermented cassava, gundruk, khalpi and kefir, present antioxidant properties. These foods contain Lactobacillus and many bioactive compounds which activate Nrf2 expression (D. Mafra et al 2022). This is again supported by evidence from pre-clinical models, where it has been demonstrated that dietary acquisition of fermented soybeans increased Nrf2 expression, which resulted in both antioxidant and anti-fatigue effects (Cui et al 2020).…”
Section: The Impact Of the Food On Gut Microbiotamentioning
confidence: 85%
“…Fermented foods based on lactic acid bacteria, such as sauerkraut, pickled cabbages, fermented cassava, gundruk, khalpi and kefir, present antioxidant properties. These foods contain Lactobacillus and many bioactive compounds which activate Nrf2 expression (D. Mafra et al 2022). This is again supported by evidence from pre-clinical models, where it has been demonstrated that dietary acquisition of fermented soybeans increased Nrf2 expression, which resulted in both antioxidant and anti-fatigue effects (Cui et al 2020).…”
Section: The Impact Of the Food On Gut Microbiotamentioning
confidence: 85%
“…Fermented foods, such as dairy, fruits and vegetable-based fermented food, contain bacteria with probable probiotic effects [ 91 ]. Experimental studies show that fermented foods may mitigate many complications associated with CKD progression and gut dysbiosis [ 92 , 93 , 94 ].…”
Section: Gut Microbiota Modulation and Effects On Residual Kidney Fun...mentioning
confidence: 99%